Sosialisasi Terapi Menulis Ekspresif Sebagai Pendekatan Self-Healing untuk Meningkatkan Kesehatan Mental Mahasiswa - Siska Putri Belangi (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
Self-healing refers to a process of treatment or healing that is carried out by oneself through a process of self-confidence and is also supported by a supportive environment and external factors. The implementation of the activity "Socialization of Expressive Writing Therapy as a Self-Healing Approach to Improve Student Mental Health" started with socialization, discussion and ice breaking carried out on 10-12 February 2024. This outreach activity was attended by approximately 40 participants. The extension participants seemed enthusiastic about the materials presented by the resource persons and were able to be actively involved, so that this extension activity took place in a two-way system and many participants asked questions. The presentation of the counseling material was followed by discussion and ice breaking to the participants who were active during the discussion activities.